2006
DOI: 10.1097/01.jcp.0000204332.64390.f3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning in Bipolar Patients Receiving Lamotrigine

Abstract: Despite the increasing use of lamotrigine (LTG) in bipolar disorder, little is known about its impact on cognition in bipolar patients. Therefore, we have evaluated 33 bipolar I and II patients on cognitive measures (verbal memory, attention, executive functions) while receiving either LTG (n = 15) or another anticonvulsant (carbamazepine or valproate; n = 18). Patients receiving LTG were generally diagnosed as having bipolar II disorder, had experienced more depressive episodes but a lesser number of hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 26 publications
2
20
0
3
Order By: Relevance
“…In healthy controls (Aldenkamp et al, 2002) and in animal models (Shannon and Love, 2004) lamotrigine appears to be associated with no significant changes in cognitive performance. In patients with bipolar disorder, both improvement (Daban et al, 2006) and worsening of cognitive performance (Osuji et al, 2007, in press) have been reported with lamotrigine. A study in HIV-positive patients with cocaine use reported no change in RAVLT performance with lamotrigine (Margolin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy controls (Aldenkamp et al, 2002) and in animal models (Shannon and Love, 2004) lamotrigine appears to be associated with no significant changes in cognitive performance. In patients with bipolar disorder, both improvement (Daban et al, 2006) and worsening of cognitive performance (Osuji et al, 2007, in press) have been reported with lamotrigine. A study in HIV-positive patients with cocaine use reported no change in RAVLT performance with lamotrigine (Margolin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Lamotrigine appears to be cognitively benign 41 , whereas topiramate, which is not indicated for bipolar disorder but may be prescribed for prevention of migraine headaches or weight control, is associated with extensive adverse cognitive effects 37 .…”
Section: Challenges and Recommendations For Trial Design In Bipolar Dmentioning
confidence: 99%
“…Changes in brain activation during working memory and facial recognition tasks in patients with bipolar disorder with LMG monotherapy have been reported (Haldane et al, 2008). Preliminary results suggest a safer neurocognitive profile of LMG on bipolar patients, as compared with other anticonvulsants (Daban et al, 2006).…”
Section: Discussionmentioning
confidence: 96%